Analisa Rugi-Rugi Serat Optik Sebagai Potensi Aplikasi Sensor Weigh In Motion (WIM) Lima Lekukan - Deajeng Wulandari, Mohtar Yunianto, Hery Purwanto (Jurnal Teori dan Aplikasi Fisika, 2013)
Fiber optic loss yielded from macrobending with fivebending model prototype. The purpose this study is to determine the influence of scratches variation toward the loss as a potential Weigh In Motion (WIM) sensor applications to plastic optical fiber (POF) diameter 0,5mm.. Pressure influence toward POF loss done up to 2 mm shift. LED, as light source, transmits the light through the fiber and received by LDR as detector. The output is voltage displayed on the computer. Pressure caused by a shift made the fiber is depressed and formed fivebending so that the loss is greater. Two scratch, three scratch, without a scratch have applied. The study result show that the more scratches, the loss was greater . Every the loss value caused by giving certain mass. The highest sensitivity when three scratches was applied which has correlation coefficient R2 0,99744 with gradient 1,2264 so this model have has the potential in Weigh In Motion (WIM) sensor applications. Keyword: POF, scratches, five bending, WIM